Activity-Based Protein Profiling for the Identification of Novel Carbohydrate-Active Enzymes Involved in Xylan Degradation in the Hyperthermophilic Euryarchaeon Thermococcus sp. Strain 2319x1E - Klaus, Thomas; Ninck, Sabrina; Albersmeier, Andreas; Busche, Tobias; Wibberg, Daniel; Jiang, Jianbing; Elcheninov, Alexander G.; Zayulina, Kseniya S.; Kaschani, Farnusch; Bräsen, Christopher; Overkleeft, Herman S.; Kalinowski, Jörn; et al. (Frontiers in Microbiology, 2022)
ABPP has so far scarcely been applied in Archaea in general and, especially, in extremophilic organisms. We herein isolated a novel Thermococcus strain designated sp. strain 2319x1E derived from the same enrichment culture as the recently reported Thermococcus sp. strain 2319x1. Both strains are able to grow with xylan as the sole carbon and energy source, and for Thermococcus sp. strain 2319x1E (optimal growth at 85 °C, pH 6-7), the induction of xylanolytic activity in the presence of xylan was demonstrated. Since the solely sequence-based identification of xylanolytic enzymes is hardly possible, we established a complementary approach by conducting comparative full proteome analysis in combination with activity-based protein profiling (ABPP) using α- or β-glycosidase selective probes and subsequent mass spectrometry (MS)-based analysis. This complementary proteomics approach in combination with recombinant protein expression and classical enzyme characterization enabled the identification of a novel bifunctional maltose-forming α-amylase and deacetylase (EGDIFPOO_00674) belonging to the GH57 family and a promiscuous β-glycosidase (EGIDFPOO_00532) with β-xylosidase activity. We thereby further substantiated the general applicability of ABPP in archaea and expanded the ABPP repertoire for the identification of glycoside hydrolases in hyperthermophiles.